An English Reading Material Analysis Through Microlearning and Critical Thinking Skill Views - Deirra Ayu Kusmana Kusmana; Ratna Dewanti; Siti Drivoka Sulistyaningrum (Universitas Lancang Kuning, 2023)
The other advantages of microlearning included improving critical thinking, reducing cognitive load, concentrating on learning, and closing the theory-practice gap. This study looks into Symphony 1, an English course book, to assess how much reading involves microlearning and critical thinking skills. The cognitive domain of Anderson and Krathwohl revised Bloom's Taxonomy, which has been modified with critical thinking skills, served as the instrument for this descriptive qualitative study. The Microlearning descriptor, which was used as the second instrument, was taken from several pertinent sources. The researcher then determined the frequency and percentage of the cognitive domain of the data under investigation. According to the research, Symphony 1 contains 42 data on microlearning and 44 data on critical thinking skills. In the meantime, the proportion of each technique varies for both features. It proved that the existing learning materials actually contain critical thinking skills and microlearning. However, each chapter of the book needs to balance and emphasize how much of each indicator is used. The study suggests that textbook authors stress microlearning ideas and critical thinking skills more so as a way to enhance students' reading experiences.